The content of antimicrobial proteins in children with respiratory tract inflammatory diseases - G.A. Lezhenko; A.Ye. Abaturov; E.Ye. Pashkova; K.V. Gladun (Zaslavsky O.Yu., 2017)
Background. Inflammatory diseases of the respiratory tract are often associated with impaired synthesis of antimicrobial peptides, whose representatives are defensins and lactoferrin (LF). The purpose of the study was to establish the concentrations of antimicrobial peptides in the oropharyngeal secretion and plasma in children with inflammatory diseases of the respiratory tract. Materials and methods. The study group included 111 children aged 4 to 17 years from orphanages. Сontent of antimicrobial proteins of LF, α-defensins 1-3 (human neutrophil peptides (HNP) 1-3), secretory immunoglobulin A in the oropharyngeal secretion, HNP 1-3 in the blood plasma, of interleukin 6 (IL-6) and -10 in the blood serum in children was measured by immunoassay. Results. Analysis of anamnestic data in somatically healthy children from orphanages showed the presence of 4 to 6 episodes of acute respiratory infections throughout the year, the duration of which averaged 5.3 ± 0.4 days. According to the results of the study, the content of α-defensins 1-3 in the blood plasma of the children of the control group was 3583.3 ± 735.4 pg/ml, while in the group of children with recurrent bronchitis, the HNP 1-3 level was almost twice higher - 6576.7 ± 602.8 pg/ml, p - 0.01. When studying the serum cytokine profile, it was found that in children with recurrent bronchitis compared with the control group, the content of proinflammatory IL-6, which regulates the inflammatory process and provides mobilization of the inflammatory response, as well as an antigen-specific immune response, had only a tendency to increase (10.1 ± 2.0 pg/ml vs 9.1 ± 1.1 pg/ml in the control group, p > 0.05). Against this background, we observed more than 3-fold increase in the level of anti-inflammatory IL-10, which is a product of type 2 helper cells, responsible for the formation of a humoral antigen-specific immune response, - 4.42 ± 1.00 pg/ml vs 1.41 ± 0.59 pg/ml, respectively (p - 0.05). Conclusions. It was found that sickly children had been characterized by the changes of mucosal protection, low content of α-defensins 1-3 in oropharyngeal secretions. The revealed changes indicated the stress of the local defense mechanisms. The investigation has revealed that overproduction of HNP 1-3 in children with recurrent bronchitis against the background of the disturbed balance between pro- and anti-inflammatory cytokines could be one of the causes of recurrent forms of the respiratory tract infection.